Biological variables influencing the estimation of reference limits - Porsch-Özçürümez, Mustafa Kemal; Haeckel, Rainer (The Scandinavian journal of clinical & laboratory investigation, 2018)
Reference limits (RLs) are required to evaluate laboratory results for medical decisions. The establishment of RL depends on the pre-analytical and the analytical conditions. Furthermore, biological characteristics of the sub-population chosen to provide the reference samples may influence the RL. The most important biological preconditions are gender, age, chronobiological influences, posture, regional and ethnic effects. The influence of these components varies and is often neglected. Therefore, a list of biological variables is collected from the literature and their influence on the estimation of RL is discussed. Biological preconditions must be specified if RL are reported as well for directly as for indirectly estimated RL. The influence of biological variables is especially important if RL established by direct methods are compared with those derived from indirect techniques. Even if these factors are not incorporated into the estimation of RL, their understanding can assist the interpretation of laboratory results of an individual.